2019
DOI: 10.1038/s41598-019-53163-9
|View full text |Cite
|
Sign up to set email alerts
|

De novo cancer incidence after kidney and liver transplantation: Results from a nationwide population based data

Abstract: The cancer risk among solid organ transplantation recipients in East-Asia has been insufficiently studied. This study estimated de novo cancer incidence in kidney and liver recipients 2008–2015, compared with the general population in Korea using nationwide data. This is a retrospective cohort study using nationwide health insurance claims data. The study population was comprised of cancer-free 10,085 kidney recipients and 3,822 liver recipients. Standardized incidence ratio (SIR) of cancer using indirect stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 45 publications
2
26
0
4
Order By: Relevance
“…In the present study, a comprehensive analysis of PTM after kidney transplantation was conducted based on nationwide data from Korea with a lengthy follow-up duration and information on mortality. The SIR of PTM was 3.9, similar to previous studies 11 , 16 , 17 . The SMR of total PTM was 1.4, and that of lymphoma showed the highest value (9.3 for Hodgkin lymphoma and 5.5 for NHL).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study, a comprehensive analysis of PTM after kidney transplantation was conducted based on nationwide data from Korea with a lengthy follow-up duration and information on mortality. The SIR of PTM was 3.9, similar to previous studies 11 , 16 , 17 . The SMR of total PTM was 1.4, and that of lymphoma showed the highest value (9.3 for Hodgkin lymphoma and 5.5 for NHL).…”
Section: Discussionsupporting
confidence: 90%
“…Regarding the types of PTM, the most common malignancy was thyroid cancer, followed by colorectal, kidney, stomach, and prostate cancer. The high frequency of these cancers demonstrated previously 16 , 17 may result from increased surveillance.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Among the adult recipients, cancer incidence increases further along the time from transplantation [ 24 ], which is at least partly explained by the higher incidence of cancer at older age in general. In the present study, the majority of cancers were diagnosed at young adult age, and a study by Park et al [ 25 ] showed that highest risk for post-transplant malignancy was among transplant age group 0–19 years.…”
Section: Discussionsupporting
confidence: 51%
“…Supplementary Table S3 provides details of the included studies, which involved e1848068-2 a total of 2,105,122 solid organ transplant recipients and reported 45 types of site-specific cancer. Of them, 52 studies 7,8,75 provided SIRs of multiple cancers of solid organ transplantations (11 for multiple organs, 7,8,[17][18][19][20][21][22][23][24][25] 19 for kidney, [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] 16 for liver, [45][46][47][48][49][50][51][52][53][54][55]75 7 for heart and/or lung [60][61][62][76]…”
Section: Systematic Search and Study Characteristicsmentioning
confidence: 99%